Evaluation of Habitat Preferences of Invasive Macrophyte Egeria densa in Different Channel Slopes Using Hydrogen Peroxide as an Indicator - Asaeda, Takashi; Senavirathna, M. D. H. Jayasanka; Vamsi Krishna, Lekkala (Frontiers in Plant Science, 2020)
Egeria densa is an often-found invasive species in Japan, which has spread widely in the past two decades in rivers where no macrophytes had previously been found. As a result, these ecosystems have now become dominated by E. densa. The habitat preference for E. densa colony formation was investigated using the tissue concentrations of hydrogen peroxide (H2O2: a reactive oxygen species) under varying conditions in rivers and laboratory conditions. The empirical equations that can describe the macrophyte tissue H2O2 formation under various velocity and light conditions were produced. The H2O2 concentrations of dark-adapted plants are proportional to the flow velocity, and the surplus H2O2 concentration in the light-exposed condition corresponded to the photosystems produced H2O2. When the H2O2 concentration exceeds 16 µmol/gFW, plant tissue starts to deteriorate, and biomass declines, indicating the critical values required for long-term survival of the plant. The empirically obtained relationships between flow velocity or light intensity and the analysis of H2O2 concentration for different slopes and depths of channels found that the H2O2 value exceeds the critical H2O2 concentration in channels with above 1/100 at around 0.6 m depth. This agrees with the observed results where colonies were not found in channels with slopes exceeding 1/100, and biomass concentration was the largest at depths of 0.6 to 0.8 m. H2O2 concentration is quite applicable to understanding the macrophyte condition in various kinds of macrophyte management.